Proporsi Pekerja Migran dan Faktor Ekonomi terhadap Tingkat Pengangguran Terbuka di Indonesia - Tri Adhi Suryo Nugroho; Made Dwi Setyadhi Mustika (BADAN PENERBIT STIEPARI PRESS, 2026)
The Open Unemployment Rate (TPT) is one of the main indicators in assessing labor market conditions and economic stability in Indonesia. This study aims to comprehensively analyze the influence of the proportion of migrant workers, Human Development Index (HDI), economic growth rate, and Provincial Minimum Wage (UMP) on TPT, by comparing the period before and after the Covid-19 pandemic. The data used is panel data from 34 provinces in Indonesia during the 2015–2024 period. The analysis was carried out using the panel data regression method using EViews software to obtain accurate, measurable, and reliable results. The results of the study showed that the proportion of migrant workers and HDI did not have a significant influence on TPT. On the other hand, the economic growth rate and UMP have a significant negative effect on the TPT, which means that an increase in both variables can reduce unemployment. In addition, the Covid-19 dummy variable has a significant positive influence on TPT, showing that the pandemic has had a real and profound impact on the increasing unemployment rate in Indonesia.